Violência no trabalho em Centros de Saúde da Família e suas interfaces com as condições e a organização do trabalho - Olimpio, Anny Caroline dos Santos (2022)
Violence in the workplace is already considered a serious social problem of a global nature and is characterized by being a multifaceted and complex multidimensional phenomenon. Based on this conception, the aim was to analyze the exposure of health workers to violence at work in the Family Health Centers and their interfaces with the conditions and organization of work. Descriptive research with a quantitative approach and developed at the Family Health Centers in Sobral, Ceará. The sample with 125 professionals being: doctors, nurses and nursing technicians who fit the inclusion criteria. Data collection was applied through the Survey Questionnaire Workplace Violence in the Health Sector. Data were coded and transferred to Microsoft Windows Excel® software and analyzed using the Statistical Package for the Social Sciences software. The ethical and legal precepts present in Resolution No. 466/2012 and No. 510/2016 of the National Health Council with CAAE number: 117741/2020 were followed. The results show that 90.3% of the sample were women, only 9.6% were men. Violence was present with 48.8%, it was noted that verbal violence (54.1%) was the most cited, followed by verbal and moral violence (36.07%), and the main perpetrators were patients. Most victims reacted to an act of violence, however only half reported the incident to the manager. It is concerned about the high degree of dissatisfaction of victims with the way the incident was handled, since for 78% these could have been avoided. It is shown that 53% of the participants reported that there were no specific behaviors to protect against violence at work and that those that existed could be greatly improved. The present study points out that there is low and/or no stimulus to reports of violence during working hours. The implementation of organizational interventions in the Family Health Centers is recommended, based on Permanent Health Education, focusing on improving communication techniques, dealing with stress and/or conflict resolution to manage workplace violence.